The bacterial burden of worn face masks—observational research and literature review - Kisielinski, Kai; Wojtasik, Barbara; Zalewska, Aleksandra; Livermore, David M.; Jurczak-Kurek, Agata (Frontiers in Public Health, 2024)
IntroductionFacemasks were widely mandated during the recent SARS-CoV-2 pandemic. Especially the use by the general population is associated with a higher risk of improper handling of the mask and contamination and potential adverse microbiological consequences.MethodsWe investigated and quantified bacterial accumulation in facemasks used by the general population, using 16S rRNA (Sanger Sequencing), culture and biochemical analysis along with Rose Bengal staining. Additionally, a systematic overview of the literature on face mask contamination was undertaken.ResultsWe found an average bacterial load of 4.24 × 104 CFU recovered/mask, with a maximum load of 2.85 × 105 CFU. This maximum is 310 times higher than the limit value for contamination of ventilation system outlet surfaces specified by the German standard VDI 6022. Biochemical and molecular identification predominantly found Staphylococcus species (80%), including Staphylococcus aureus, along with endospore-forming Bacillus spp. Literature reports also indicate contamination of masks by bacterial and fungal opportunists of the genera Acinetobacter, Aspergillus, Alternaria, Bacillus, Cadosporium, Candida, Escherichia, Enterobacter, Enterococcus, Klebsiella (including K. pneumoniae), Micrococcus, Microsporum, Mucor, Pseudomonas, Staphylococcus and Streptococcus. Bacterial counts increase linearly with wearing duration.DiscussionProlonged use may affect the skin and respiratory microbiomes, promoting consequential eye, skin, oral and airway conditions. These aspects underscore the urgent need for further research and a risk-benefit analysis in respect of mask use, particularly given their unproven efficacy in disrupting the transmission of respiratory viruses and their adverse social consequences.